Handbook of flotation reagents : chemistry, theory and practice. [Volume 2], - Bulatovic, Srdjan M. (Elsevier, 2010)
Handbook of Flotation Reagents: Chemistry, Theory and Practice is a condensed form of the fundamental knowledge of chemical reagents commonly used in flotation and is addressed to the researchers and plant metallurgists who employ these reagents. This book consists of three distinct parts: part 1 provides detailed description of the chemistry used in mineral processing industry; part 2 describes theoretical aspects of the action of flotation reagents, while part 3 provides information on the use of reagents in over 100 operating plants treating Cu, Cu/Zn, Cu/Pb, Zn, Pb/Zn/Ag, Cu/Ni and Ni ores. Written in a clear, easy-to-follow format, Handbook of Flotation Reagents: Chemistry, Theory and Practice is an indispensable reference for any professional working with flotation reagents. In a number of chapters, data from innovative technology is presented. Looks at the theoretical aspects of flotation reagents Examines the practical aspects of using chemical reagents in operating plants Provides guidelines for researchers and engineers involved in process design and development.
Includes index.
Keywords: Flotation reagents.; elektronické knihy; electronic books